Land Contamination and Brownfield Management Policy Development in China: Learning from the UK Experience - Coulon, Frederic; Bardos, Paul; Harries, Nicola; Canning, Kate; Chen, Mengfang; Hu, Qing; Jones, Kevin C.; Li, Fasheng; Li, Hong; Gomes, Diogo M.; Liu, Ming; Liu, Rongxia; et al. (Cranfield University, 2016)
Over the last 30 years, China’s fast urbanisation along with huge expansion of its manufacturing industry has led to the emergence of significant soil and water contamination problems across China. In the meantime, a number of policies and regulatory agencies for the protection of the environment have been implemented to stop deliberate pollution and more recently to address pollution prevention at source on a wider scale. Soil protection and management have been featured in policy discussions since the late 1950s in China. However, the topic has recently been of greatly expanded interest in the development of emerging policies, particularly with regards to the role of soil as a resource, independent of the functions that it carries out. Soil provides multiple important functions such as provision of food and raw materials, a platform for urban development and human wellbeing and a filtering and transforming media for water, nutrients, and carbon. However as pointed out by Yuan Si, Deputy Director of the Environmental Protection and Resources Conservation Committee of the National People Congress (China Daily, 11 March 2016), the move toward integrated management that has been driving policies for air and water has proven to be a challenge for soil management, mainly due to the multiple functions that soils provide. This is also true internationally and explained by several drivers for soil protection including among others soil contamination, construction, agriculture and amenity value.
Ming Liu (Department of Science, Technology & Innovation, British Consulate-General Guangzhou), Xia Yang (Administrative Centre for China’s Agenda21) and Paul Wills (UK Trade & Investment) helped discussion and revision of the report. Diogo Gomes (Cranfield University) also provided support for the graphical arts and assisted with the editing. The authors are grateful to all partners of the SPF project which include a wide team of collaborators and advisors across China and UK for their useful discussions and contribution during the two workshops organised during the project. Government, Academia, Industry and Public bodies have been collaborating together to drive structural changes far beyond the scope of a single organisation.
Keywords: environmental management; Soil science; sustainable remediation